Role of RNA in enzymatic activity of the reverse transcriptase of hepatitis B viruses. - Wang, G H (1994)
The hepadnavirus reverse transcriptase is a multifunction enzyme. In addition to its role in DNA synthesis, the polymerase is required for RNA packaging and also functions as the primer for minus-strand DNA synthesis. Previously, we demonstrated that the protein-priming activity of the polymerase requires a viral RNA segment, termed epsilon, which serves as a template for the synthesis of a short DNA oligomer that is covalently attached to the reverse transcriptase (G.-H. Wang and C. Seeger, J. Virol. 67:6507-6512, 1993). We now report that epsilon is sufficient for activation of the reverse transcriptase to prime DNA synthesis through the formation of a stable RNA-protein (RNP) complex. We also demonstrate that the binding reaction depends on sequence-specific determinants on epsilon. Moreover, our results indicate that two genetically separated domains of the reverse transcriptase are required for formation of the RNP complex. Finally, we show that the polymerase has a DNA polymerase activity in the absence of epsilon which does not depend on the protein-priming mechanism.